Fostering Understanding Between the Provost’s Office and Department Heads - Devon Brenner; Jerry Gilbert; Julia Hodges (Academic Chairpersons Conference Proceedings, 2015)
Sharing a variety of formal and informal programs for department head/provost’s office communication and ways to make the most of each.
Keywords: Communication; administration; dialogue; provost; discussion